2017
DOI: 10.1007/s00203-017-1414-x
|View full text |Cite
|
Sign up to set email alerts
|

Kribbella sindirgiensis sp. nov. isolated from soil

Abstract: A Kribbella strain FSN23 was isolated from soil sample which was collected from Caygoren Dam lakeside located in Sındırgı, Turkey. The isolate was investigated using a polyphasic approach consisting of numeric, chemotaxonomic and molecular analysis. The isolate indicated chemotaxonomic, morphological and phylogenetic properties associated with members of the genus Kribbella. Phylogenetic analysis based on the 16S rRNA sequence of the strain demonstrated that the strain forms a subclade with K. aluminosa HKI 04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The Actinobacteria phylum has diverse physiological properties, such as the production of extracellular enzymes for the decomposition of organic matter [75]. It has also been shown that Actinobacteria abundance is associated with the respiration rates of the soil [76,77], which agrees with the current study, since CO 2 emission was greater under Conv management. Regarding bacterial genera that were more abundant in soil under Org management, Gemmata is capable of using glucose and galactose as a source of carbon in order to thrive, and therefore it is an important producer in the carbon and N cycles [78,79].…”
Section: Abundance Of Bacterial Taxasupporting
confidence: 91%
“…The Actinobacteria phylum has diverse physiological properties, such as the production of extracellular enzymes for the decomposition of organic matter [75]. It has also been shown that Actinobacteria abundance is associated with the respiration rates of the soil [76,77], which agrees with the current study, since CO 2 emission was greater under Conv management. Regarding bacterial genera that were more abundant in soil under Org management, Gemmata is capable of using glucose and galactose as a source of carbon in order to thrive, and therefore it is an important producer in the carbon and N cycles [78,79].…”
Section: Abundance Of Bacterial Taxasupporting
confidence: 91%
“…However, the genus Flavisolibacter has previously been reported in cultivated soils [ 99 ]. The genera Aeromicrobium and Kribbella (belonging to the Actinobacteria) have also been isolated from alkaline soils [ 100 , 101 ] similar to Loess alkaline agricultural soils. The specific functions of these keystone taxa still remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Kribbella and Niastella (corresponding to ASV-B3 in Table S3 ) have been identified as a nitrate reducer and denitrifier, respectively ( Nishizawa et al , 2014 ; Ozdemir-Kocak et al , 2017 ). Increases in the abundance and activities of these bacteria in a rhizosphere are not favorable from the viewpoint of agriculture because their effects on mineral nitrogen may reduce the efficiency of nitrogen fertilization.…”
mentioning
confidence: 99%